Critical microstructural modifications of Cu/Zn/Al2O3 catalyst during CO2 hydrogenation to methanol - Barros, João L.M.; Neto, Olavo T.; Archanjo, Bráulio S.; Kuznetsov, Oleksii; dos Santos, João B.O.; Franchini, Carlos A.; Corat, Evaldo J.; Silva, Adriana M. (Catalysis today, 2024)
This contribution reports the impact of the reaction pressure (1, 10, 20 and 30 bar) on the deactivation of the commercial catalyst Cu/ZnO/Al2O3 during the CO2 hydrogenation to CH3OH. The best performance was obtained at 30 bar with ≈ 30 % of initial CO2 conversion (XCO2) and CH3OH space-time-yield (STYMEOH) of 255 mgMeOH/gcat.h. Although the initial conversion decreased drastically the activity was kept along all the reaction time, ≈ 5 %. The analysis of fresh and post-reaction samples using X-ray Diffraction (XRD), Thermogravimetric Analysis (TGA), Electron Microscopy (SEM-FEG, STEM, HRTEM), and Raman Spectroscopy demonstrated profound microstructural changes, characterized by phase sintering, formation of Cu-aluminate, segregation of phases, an imbalance among Cu-species, as well as the presence of coke. As the catalyst Cu/ZnO/Al2O3 has a particular microstructure, these modifications provoked the loss of the geometric configuration of the active sites, which might also originate a disturbance in the electronic interactions, resulting in activity loss. HRTEM and STEM image (dark field) of the passivated sample showed the presence of crystalline nanostructures (d < 4 nm) attributed to Cu0, surrounded by amorphous phases. STEM images of spent samples also reveals the development of hierarchical and elongated nanostructures spread on all the spent catalysts. This result foresees the co-existence of small nanoparticles (< 5 nm) with large ones in all the catalyst surface, corroborating XRD results. It is noteworthy that the hydrothermal environmental developed inside the reactor originated from the high pressure and the continuous H2O production, both which may favor the phase sintering and aluminate formation. [Display omitted] •Deep microstructural modifications of catalysts components.•Development of hierarchical nanostructures of Cu and Zn under reaction conditions.•Formation of inactive Cu-aluminates.•Segregation of phases ZnO and Al2O3.•All the mentioned modifications led to a drop on the catalyst performance but still keeping the activity under TOS.